Analisis Kualitas Briket Biomassa dari Limbah Sekam Padi dan Daun Kering sebagai Sumber Energi Baru Terbarukan - Apriani, Enda; Andika, Markus Nanda (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
Rice husk waste and dry leaves can be found all around us. If not managed properly, it can pollute the environment. For this reason, this waste can be used to make products with economic value, for example briquettes are an alternative energy source. The trial design for making briquettes in this study used a comparison ratio (75: 25). Mixing rice husk charcoal and ground dry leaves with a ratio of 75% rice husk charcoal and 25% dry leaf charcoal, as well as adding 5% tapioca adhesive and 30% water. The briquette compression test results show that sample 1 with a maximum force of 6038.5 N has the highest compression value of 9.67 Mpa. Sample 2 with a maximum force of 713.46 N produces a compression value of 1.88 Mpa, while sample 3 with a maximum force of 1121.14 N has a compression value of 3.00 Mpa. The result is that sample 1 has the highest pressure value. The results of observing the microstructure using SEM testing showed that the size was larger, namely at 50x magnification compared to other particle size magnifications (300x, 500x 800x, and 1,000x), namely 500 µm.  Keywords: Briquettes, dry leaves, pressure test, rice husk waste, SEM test